Porfirinas de manganês hidrofóbicas como catalisadores da oxidação de substratos orgânicos por vias mais sustentáveis - Adriano Silva Guimarães (2019)
Several studies related to (metallo) porphyrins have been carried out by several research groups and among them, there is the use of the cytochrome P450 as biomimetic model, responsible for the oxidation of substances exogenous to organisms. Therefore, the focus of this work was the acquisition of new manganese metalloporphyrins and their use as catalysts in the oxidation reactions of two organic substrates: cyclohexane and carvacrol.In an innovative way, we looked for more sustainable routes for the oxidation of the compounds, that is, according to some principles of Green Chemistry. Two unpublished hydrophobic porphyrins, H2T2,3,4TMPP and H2T2,4,5TMPP, containing the methoxy substituents (-OCH3) at the 2,3,4 or 2,4,5 positions of the aryl group, located at the same meso positions of the macrocycle, and the respective manganese complexes were obtained.Through analysis techniques, it was possible to characterize the four synthesized compounds. The manganese complexes [MnIII(T2,3,4TMPP)Cl] (Cat3), [MnIII(T2,4,5TMPP)Cl] (Cat2) e [MnIII(TPP)Cl](Cat1, containing only the phenyl group at positions meso), were used as catalysts in cyclohexane oxidation reactions by iodosilbenzene (PhIO), iodobenzene diacetate (PhI(OAc)2)and Oxone®, using green solvents (ethyl acetate and dimethyl carbonate) and dichloromethane, as well as in the absence of solvents.The influence of water and imidazole additives was also evaluated. Cat1 and Cat2 were also used as catalysts in oxidation reactions of carvacrol by PhIO, PhI(OAc)2, hydrogen peroxide (H2O2)and tert-butyl peroxideC(CH3)3OOC(CH3)3, using the above mentioned solvents. In the oxidation reactions of cyclohexane, the systems with the oxidant PhIO and the catalysts Cat2 and Cat3, presented higher total yields for the oxygenated products when compared to those employing Cat1, in the absence or presence of any of the solvents.The Cat2/PhIO and Cat3/PhIO systems showed higher total yields for the oxygenated products when compared to those using PhI(OAc)2, in the absence of solvent and in the presence of the green solvents. Normally, the addition of water and/or imidazole allowed an improvement in the total yields for the oxygenated products for the systems with the PhIO or PhI(OAc)2oxidants.The substitution pattern 2,3,4 and/or 2,4,5 of the aryl groups, in the meso positions of the macrocycle, had little influence on the catalytic activity for the dichloromethane systems. In the oxidation reactions of carvacrol by PhIO or PhI(OAc)2, the conversion of the substrate was greater in the presence of catalysts Cat1 and Cat2 in any of the solvents studied,being Cat1 more efficient than Cat2.The conversion of carvacrol to thymokine was higher in the systems with the oxidant PhI(OAc)2in ethyl acetate and dichloromethane